'The Art of Agony': Aspects of Negativity in Grainger's Music. Issue 1 (8th June 2018) - Tregear, Peter
Abstract : Throughout his life, Grainger claimed that he sought to put his music at the service of 'the complicated facts & problems of modern life', a task he thought required engaging his audience in a 'pilgrimage to sorrow'. On the whole, however, audiences and critics alike have tended instead to associate Grainger with the works of his that sound anything but downbeat. Nevertheless, Grainger's self assessment was genuine. He had a painfully ambivalent relationship to many of the emerging features of modernity, a state of mind for which he found a fellow-traveller in Rudyard Kipling. Both men found a means to express elements of this ambivalence via an unusually strong interest in both local and foreign vernacular cultures. Grainger's original text settings and folksong arrangements alike do not merely celebrate the global reach of the British world or try to preserve the dying folk music traditions of rural England and Scandinavia, but instead are an attempt to express what he considered to be particular fissures in the modern psyche, not least his own. He believed that any lasting accommodation with the emerging features of modern life required us to confront what we had lost along the way.